Homogenizing method of composite positive electrode slurry

Through the combination of wet and semi-dry processes, the solid content and viscosity of the slurry are controlled, and the problem of uneven dispersion of lithium manganese iron phosphate and ternary materials in the composite positive electrode slurry is solved, and the stability of the slurry and battery are improved. Preparation quality.

CN119297186AActive Publication Date: 2025-01-10EVE POWER CO LTD
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202411259261.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-10
Estimated Expiration
2044-09-09

Smart Images

  • Figure BDA0005036246460000121
    Figure BDA0005036246460000121
  • Figure BDA0005036246460000131
    Figure BDA0005036246460000131
Patent Text Reader

Abstract

The invention provides a homogenizing method of composite positive electrode slurry. The homogenizing method comprises the following steps: mixing ternary slurry with lithium iron manganese phosphate slurry to prepare the composite positive electrode slurry; the preparation method of the ternary slurry comprises the following steps: adding a conductive adhesive solution into a ternary material, and carrying out stirring treatment to prepare the ternary slurry with the solid content of 76-80% and the viscosity of 4000-7000 mPa.s; the preparation method of the lithium manganese iron phosphate slurry comprises the following operations: performing dry mixing on lithium manganese iron phosphate and a second conductive agent, performing stirring treatment to prepare a mixed dry material, and then adding a second glue solution into the mixed dry material to prepare the lithium manganese iron phosphate slurry, the solid content of the lithium manganese iron phosphate slurry being 58-62%, and the viscosity being 7000-20000 mPa.s. According to the homogenizing method provided by the invention, the ternary materials and the lithium manganese iron phosphate with different particle sizes can be fully dispersed, so that the preparation yield of the composite positive electrode slurry is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to a method for homogenizing a composite positive electrode slurry. Background Art

[0002] In recent years, with the widespread application of lithium batteries in the field of power and energy storage batteries, safety issues have become increasingly prominent. Both lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) have stable olivine structures and good safety. At the same time, due to the high working voltage of manganese, the theoretical gram capacity of lithium manganese iron phosphate is 13% higher than that of lithium iron phosphate, and it is considered to be the most potential cathode material to replace lithium iron phosphate. However, lithium manganese iron phosphate still has problems such as low gram capacity and poor electrochemical performance. Because ternary materials (NCM) have similar voltage ranges to lithium manganese iron phosphate, researchers have tried to moderately dope ternary materials into lithium manganese iron phosphate to increase the gram capacity of composite cathode materials and improve kinetic performance. In addition, when the ternary material is doped with a small amount of ternary material, small particles of lithium manganese iron phosphate can wrap large particles of ternary materials with low thermal stability, realizing the improvement of battery energy density through material composite methods while ensuring battery safety.

[0003] However, due to the different particle sizes, structural characteristics and physical properties of lithium manganese iron phosphate and ternary materials, if lithium manganese iron phosphate and ternary materials are directly physically mixed, in the subsequent unified slurry step, it is easy to cause problems such as uneven particle dispersion and low slurry stability, which seriously restricts the battery preparation yield. Summary of the invention

[0004] The purpose of the present invention is to provide a method for homogenizing a composite positive electrode slurry, which solves the problems of uneven dispersion of lithium manganese iron phosphate and ternary materials directly physically mixed and poor slurry stability during the homogenization of the composite positive electrode slurry in the prior art.

[0005] According to another aspect of the present invention, a method for homogenizing a composite positive electrode slurry is provided, comprising the following operations: mixing a ternary slurry with a lithium iron manganese phosphate slurry to obtain a composite positive electrode slurry; wherein the method for preparing the ternary slurry comprises the following operations: adding a conductive glue to the ternary material and stirring the mixture to obtain a ternary slurry, wherein the solid content of the ternary slurry is 76% to 80%, and the viscosity is 4000 to 7000 mPa·s; the conductive glue comprises a first glue and a first conductive agent; wherein the method for preparing the lithium iron manganese phosphate slurry comprises the following operations: dry mixing the lithium iron manganese phosphate with the second conductive agent and stirring the mixture to obtain a mixed dry material, and then adding the second glue to the mixed dry material to obtain a lithium iron manganese phosphate slurry, wherein the solid content of the lithium iron manganese phosphate slurry is 58 to 62%, and the viscosity is 7000 to 20000 mPa·s.

[0006] Since lithium manganese iron phosphate (LMFP) has a small particle size, small particles of LMFP have a large specific surface area and a strong adsorption capacity, and the particles are easy to agglomerate. Therefore, the present invention prepares lithium manganese iron phosphate slurry by adopting a semi-dry homogenization process (adding a second glue solution after dry mixing LMFP and a second conductive agent), which is beneficial to promoting the uniform dispersion of LMFP particles. Based on this, by further controlling the solid content and viscosity of the lithium manganese iron phosphate slurry, the lithium manganese iron phosphate slurry has a lower solid content and a higher viscosity, which is beneficial to maintaining a good bonding strength between LMFP particles while ensuring a good dispersion effect of the LMFP particles, thereby improving the stability of the lithium manganese iron phosphate slurry. Since the particle size of the ternary material is large, the large-particle ternary material has good processing ability and is not easy to agglomerate. Therefore, the preparation of the ternary slurry by adopting the wet homogenization process (mixing the conductive glue with the ternary material) is beneficial to maintain a good van der Waals force between the conductive glue and the ternary material. Based on this, by further controlling the solid content and viscosity of the ternary slurry, it is beneficial to make the ternary slurry have good stability and fluidity. At the same time, it is convenient for the subsequent uniform homogenization of the ternary slurry with the lithium iron manganese phosphate slurry, so that the prepared composite positive electrode slurry has the advantages of high stability and uniform dispersion.

[0007] In summary, the present invention adopts a wet process to prepare a ternary slurry, a semi-dry process to prepare a manganese iron phosphate lithium slurry, and controls the solid content and viscosity of the ternary slurry and the manganese iron phosphate lithium slurry respectively, so that the composite positive electrode slurry obtained thereby has good uniformity and stability. Therefore, the homogenization method provided by the present invention is suitable for positive electrode active materials of different particle sizes, and can achieve full dispersion of ternary materials and manganese iron phosphate lithium slurry of different particle sizes, effectively avoiding the agglomeration and sedimentation of particles, so that the preparation yield of the composite positive electrode slurry is improved. In addition, the homogenization method is simple to operate, has high production efficiency, and is suitable for industrial production.

[0008] Preferably, the solid content of the ternary slurry is 77.5% to 78.5%, and the viscosity is 5500 mPa·s to 6500 mPa·s.

[0009] Preferably, the solid content of the lithium manganese iron phosphate slurry is 59.5% to 60.5%, and the viscosity is 10000 mPa·s to 14000 mPa·s.

[0010] Preferably, the ternary material includes nickel cobalt manganese oxide (NCM), and the nickel cobalt manganese oxide includes at least one of NCM333, NCM523, NCM622, and NCM811.

[0011] Preferably, the first glue solution includes a binder and a solvent.

[0012] Preferably, the second glue solution includes a binder and a solvent.

[0013] Preferably, the first conductive agent includes at least one of a first solid conductive agent and a first conductive agent slurry; the specific surface area of ​​the first solid conductive agent is 50 m 2 / g~200m 2 / g, the particle size D50 is 20nm~70nm; the specific surface area of ​​the solid conductive agent in the first conductive agent slurry is 100m 2 / g~1000m 2 / g, and the particle size D50 is 4nm to 17nm. Conductive agents with smaller specific surface area and larger particle size have better dispersion effect and are not easy to agglomerate, while conductive agents with larger specific surface area and smaller particle size have poor dispersion effect, are easy to agglomerate, and are easy to absorb solvents, which is not conducive to the fluidity of the slurry. Therefore, by preparing conductive agents with higher specific surface area and aspect ratio into conductive agent slurry and then adding them to the ternary material, it is beneficial to promote the dispersion of the conductive agent and reduce the risk of poor slurry stability and quality degradation caused by uneven dispersion of the conductive agent.

[0014] Preferably, the first conductive agent includes a first solid conductive agent, and the mass ratio of the first glue to the first solid conductive agent is (45-50): (2-5), wherein the solid content of the first glue is 5.5-6.5%, and the viscosity is 1000-1800 mPa·s. By controlling the ratio of the first glue to the first solid conductive agent in the conductive glue, as well as the solid content and viscosity of the first glue, it is beneficial to fully wet and disperse the first solid conductive agent with the first glue, and at the same time, it is beneficial to achieve effective regulation of the solid content and viscosity of the conductive glue, ensuring that the conductive glue can fully bond and disperse the ternary material added subsequently, so that the stability and uniformity of the ternary slurry prepared thereby are further optimized.

[0015] Preferably, the first conductive agent also includes a first conductive agent slurry, and the mass ratio is: first glue: first solid conductive agent: first conductive agent slurry = (45-50): (2-5): (20-30); wherein the solid content of the first conductive agent slurry is 3-8%.

[0016] Preferably, the mass ratio of the ternary material to the conductive adhesive is 70:(20-30). By controlling the mass ratio of the ternary material to the conductive adhesive, it is beneficial to maintain a strong van der Waals force between the ternary material and the conductive adhesive, and it is beneficial to control the solid content and viscosity of the ternary slurry thus prepared, so that the stability and uniformity of the ternary slurry are further optimized.

[0017] Preferably, the specific operation of adding the conductive adhesive to the ternary material is as follows: S1. Add part of the conductive adhesive to the ternary material and stir it; S2. Add part of the conductive adhesive to the mixed solution obtained after S1 is completed and stir it; S3. Add the remaining conductive adhesive to the mixed solution obtained after S2 is completed and stir it, thereby preparing a ternary slurry; wherein, the amount of the conductive adhesive is determined according to the mass of the conductive adhesive in S1: the mass of the conductive adhesive in S2: the mass of the conductive adhesive in S3 = (15-25): (35-45): (35-45). By adding the conductive adhesive to the ternary material step by step and reasonably setting the step-by-step amount of the conductive adhesive, it is beneficial to fully wet and disperse the ternary material with the conductive adhesive, so that the uniformity and stability of the ternary slurry prepared thereby are improved, and the particle agglomeration and sedimentation are prevented from adversely affecting the quality of the slurry.

[0018] Preferably, the solid content of the second glue is 7% to 10%, and the viscosity is 2000 to 4000 mPa·s. Since the particle size of lithium manganese iron phosphate (LMFP) is small and the specific surface area is large, adding the second glue with higher viscosity to the small particle LMFP is conducive to ensuring the effective bonding between the lithium manganese iron phosphate particles, improving the stability of the lithium manganese iron phosphate slurry obtained therefrom, and preventing the slurry from pulverizing, settling and other problems.

[0019] Preferably, calculated by mass fraction ratio, lithium iron manganese phosphate: second conductive agent: second glue liquid = 60: (0.2-0.8): (10-20). The second glue liquid is mixed with LMFP particles and the second conductive agent in a suitable proportion, which is conducive to effectively regulating the solid content and viscosity of the lithium iron manganese phosphate slurry, promoting the full dispersion of solid particles (LMFP particles and second conductive agent) in the lithium iron manganese phosphate slurry, and further optimizing the dispersion and uniformity of the lithium iron manganese phosphate slurry.

[0020] Preferably, in the process of preparing the ternary slurry and / or the lithium manganese iron phosphate slurry, the stirring temperature is 30-50° C. The above temperature conditions are conducive to improving the dispersibility of the solid particles in the slurry and optimizing the uniformity of the slurry.

[0021] Preferably, the particle size of the ternary material is 5 to 15 μm, and the particle size of the lithium manganese iron phosphate is 1 to 3 μm.

[0022] According to another aspect of the present invention, a composite positive electrode slurry is provided, which is prepared by the above-mentioned composite positive electrode slurry homogenization method.

[0023] According to another aspect of the present invention, a lithium battery is provided, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active coating, and the positive electrode active coating comprises the above-mentioned composite positive electrode slurry. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] Example 1

[0026] The present invention provides a composite positive electrode slurry, and the preparation method thereof comprises the following operations:

[0027] 1. Preparation of ternary slurry

[0028] (1) Preparation of the first glue solution

[0029] 117.6 kg of solvent N-methylpyrrolidone (NMP) and 7.5 kg of binder polyvinylidene fluoride (PVDF) were added into a 200 L stirring tank, with an orbital speed of 20 rpm, a rotation speed of 1000 rpm, a temperature of 45°C, and a stirring time of 300 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0030] Then, the mixture was stirred at an orbital speed of 20 rpm and an autorotational speed of 1000 rpm until the temperature dropped to 25° C., thereby obtaining a first adhesive solution having a solid content of 6.0% and a viscosity of 1400 mPa·s.

[0031] (2) Preparation of conductive adhesive

[0032] 47.9 kg of the first glue and 24 kg of the first conductive agent slurry (CNT conductive agent slurry) were added into a stirring tank, with a revolution speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45° C., and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0033] Then, 3.2 kg of the first solid conductive agent conductive carbon black (SP) was added into the stirring tank, and the revolution speed was 25 rpm, the rotation speed was 2000 rpm, the temperature was 40°C, and the stirring time was 120 minutes, so that the vacuum degree of the mixed system was ≤-0.085 MPa, and a conductive adhesive was prepared; wherein the specific surface area of ​​the first solid conductive agent was 100 m 2 / g, and particle size D50 is 35nm.

[0034] (3) Preparation of ternary slurry

[0035] S1: Add 70kg NCM (NCM particle size is 6μm) and 4.5kg conductive glue into a stirring tank, with a revolution speed of 5rpm, a rotation speed of 800rpm, a temperature of 40℃, and a stirring time of 15 minutes;

[0036] S2: Add 9kg of conductive glue into the stirring tank, with a revolution speed of 5rpm, a rotation speed of 800rpm, a temperature of 40℃, and a stirring time of 15 minutes;

[0037] S3: Add 9kg of conductive glue into the stirring tank, with a revolution speed of 15rpm, a rotation speed of 1500rpm, a temperature of 40℃, and a stirring time of 10 minutes;

[0038] S4: revolution speed 25rpm, rotation speed 2000rpm, temperature 40°C, stirring time 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085Mpa;

[0039] S5: orbital speed: 15 rpm, rotation speed 300 rpm, stirring until the temperature drops to 25°C, so that the vacuum degree of the mixed system is ≤-0.085 MPa; a ternary slurry is obtained, the solid content of the ternary slurry is 78%, and the viscosity is 6000 mPa·s.

[0040] 2. Preparation of lithium manganese iron phosphate (LMFP) slurry

[0041] Step 1: Add 0.5 kg of the second conductive agent SP and 60 kg of LMFP (the particle size of LMFP is 2 μm) into a 100 L stirring tank, with a revolution speed of 25 rpm, a temperature of 45° C., and a stirring time of 15 minutes;

[0042] Step 2: Add 22.3 kg of solvent NMP into a stirring tank, with an orbital speed of 25 rpm, a rotation speed of 500 rpm, a temperature of 45°C, and a stirring time of 15 minutes;

[0043] Step 3: orbital speed 25 rpm, rotation speed 1500 rpm, temperature 45°C, stirring time 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0044] Step 4: Add 5kg of CNT conductive agent slurry into the stirring tank, with a revolution speed of 25rpm, a rotation speed of 1500rpm, a temperature of 45°C, and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085Mpa;

[0045] Step 5: Add 15.5 kg of the second glue solution into the stirring tank, with a revolution speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45°C, a stirring time of 90 minutes, and a vacuum degree of ≤-0.085 MPa;

[0046] Step 6: The mixture was stirred at an orbital speed of 15 rpm and a rotational speed of 200 rpm until the temperature dropped to 25° C. to obtain lithium iron manganese phosphate slurry having a solid content of 60.0% and a viscosity of 12000 mPa·s.

[0047] 3. Preparation of composite cathode slurry

[0048] (1) 14.6 kg NMP, 26.4 kg ternary slurry and 80 kg lithium iron manganese phosphate slurry were added into a 200 L stirring tank, with an orbital speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45° C., and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0049] (2) The revolution speed was 20 rpm and the rotation speed was 1000 rpm, and the mixture was stirred until the temperature dropped to 25° C. to obtain the composite positive electrode slurry of this embodiment.

[0050] Example 2

[0051] This embodiment prepares a composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that: (1) the solid content of the first glue solution used in this embodiment is 5.5%, and the viscosity is 1000mPa·s; (2) the solid content of the ternary slurry prepared in this embodiment is 77.5%, and the viscosity is 5500mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0052] Example 3

[0053] This embodiment prepares a composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that: (1) the solid content of the first glue solution used in this embodiment is 6.5%, and the viscosity is 1800mPa·s; (2) the solid content of the ternary slurry prepared in this embodiment is 78.1%, and the viscosity is 6500mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0054] Example 4

[0055] This embodiment prepares composite positive electrode slurry with reference to embodiment 1. The difference between this embodiment and embodiment 1 is that in the process of preparing ternary slurry, the feeding amount of NCM is adjusted to 74.5 kg, so that the solid content of the ternary slurry prepared in this embodiment is 79% and the viscosity is 7000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in embodiment 1.

[0056] Example 5

[0057] This embodiment prepares composite positive electrode slurry with reference to embodiment 1. The difference between this embodiment and embodiment 1 is that in the process of preparing ternary slurry, the feeding amount of NCM is adjusted to 66.5 kg, so that the solid content of the ternary slurry prepared in this embodiment is 77% and the viscosity is 5000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in embodiment 1.

[0058] Example 6

[0059] This embodiment prepares the composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of preparing the ternary slurry in this embodiment, the mass of the conductive glue in S1: the mass of the conductive glue in S2: the mass of the conductive glue in S3 = 10:45:45. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0060] Example 7

[0061] This embodiment prepares the composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of preparing the ternary slurry in this embodiment, the mass of the conductive glue in S1: the mass of the conductive glue in S2: the mass of the conductive glue in S3 = 30:35:35. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0062] Example 8

[0063] This embodiment prepares the composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of preparing the ternary slurry, the conductive carbon black (SP) is replaced by carbon nanotubes (CNT) of the same mass as the first solid conductive agent, and the specific surface area of ​​the carbon nanotubes is 200m 2 / g, and the particle size D50 is 10nm. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0064] Example 9

[0065] This embodiment prepares a composite positive electrode slurry with reference to Example 1. The differences between this embodiment and Example 1 are: (1) the solid content of the second glue solution used in this embodiment is 7% and the viscosity is 2000 mPa·s; (2) the solid content of the lithium manganese iron phosphate slurry prepared in this embodiment is 59.85% and the viscosity is 10000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0066] Example 10

[0067] This embodiment prepares a composite positive electrode slurry with reference to Example 1. The differences between this embodiment and Example 1 are: (1) the solid content of the second glue solution used in this embodiment is 10%, and the viscosity is 3000 mPa·s; (2) the solid content of the lithium manganese iron phosphate slurry prepared in this embodiment is 60.2%, and the viscosity is 13000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0068] Embodiment 11

[0069] This embodiment prepares the composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of preparing the lithium manganese iron phosphate slurry, the feeding amount of LMFP is adjusted to 57.6 kg so that the solid content of the prepared lithium manganese iron phosphate slurry is 59% and the viscosity is 7000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0070] Example 12

[0071] This embodiment prepares the composite positive electrode slurry with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of preparing the lithium manganese iron phosphate slurry, the feeding amount of LMFP is adjusted to 62.5 kg so that the solid content of the prepared lithium manganese iron phosphate slurry is 61% and the viscosity is 17000 mPa·s. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0072] Comparative Example 1

[0073] This comparative example provides a composite positive electrode slurry, and the preparation method thereof comprises the following operations:

[0074] (1) Add 0.5 kg of conductive agent SP, 42 kg of LMFP, and 18 kg of NCM into a 100 L stirring tank, with a revolution speed of 25 rpm, a temperature of 25 °C, and a stirring time of 15 minutes;

[0075] (2) Add 22.3 kg of NMP into a stirring tank, with an orbital speed of 25 rpm, a rotation speed of 500 rpm, a temperature of 25° C., and a stirring time of 15 minutes;

[0076] (3) Revolution speed 25 rpm, rotation speed 1500 rpm, temperature 45°C, stirring time 120 minutes, vacuum degree ≤ -0.085 MPa;

[0077] (4) Add 5 kg of CNT conductive agent slurry into a stirring tank, with a revolution speed of 25 rpm, a rotation speed of 1500 rpm, a temperature of 45 ° C, a stirring time of 120 minutes, and a vacuum degree of ≤-0.085 MPa;

[0078] (5) 15.5 kg of the second glue prepared in Example 1 was added into a stirring tank, with an orbital speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45° C., a stirring time of 90 minutes, and a vacuum degree of ≤-0.085 MPa;

[0079] (6) The revolution speed was 15 rpm, the rotation speed was 200 rpm, and the mixture was stirred until the temperature dropped to 25° C. to obtain the composite positive electrode slurry of this comparative example; the solid content of the composite positive electrode slurry was 60.0% and the viscosity was 5000 mPa·s.

[0080] Comparative Example 2

[0081] This comparative example refers to Example 1 to prepare a composite positive electrode slurry. The difference between this comparative example and Example 1 is that this comparative example refers to the preparation method of lithium iron manganese phosphate slurry in Example 1 to prepare a ternary slurry; and refers to the preparation method of lithium iron manganese phosphate slurry in Example 1 to prepare a ternary slurry. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0082] The specific method for preparing the composite positive electrode slurry in this comparative example is as follows:

[0083] 1. Preparation of lithium manganese iron phosphate (LMFP) slurry

[0084] (1) Preparation of the first glue solution

[0085] 117.6 kg of solvent N-methylpyrrolidone (NMP) and 7.5 kg of binder polyvinylidene fluoride (PVDF) were added into a 200 L stirring tank, with an orbital speed of 20 rpm, a rotation speed of 1000 rpm, a temperature of 45°C, and a stirring time of 300 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0086] Then, the mixture was stirred at an orbital speed of 20 rpm and an autorotational speed of 1000 rpm until the temperature dropped to 25° C., thereby obtaining a first adhesive solution having a solid content of 6.0% and a viscosity of 1400 mPa·s.

[0087] (2) Preparation of conductive adhesive

[0088] 47.9 kg of the first glue and 24 kg of the first conductive agent slurry (CNT conductive agent slurry) were added into a stirring tank, with a revolution speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45° C., and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0089] Then, 3.2 kg of the first solid conductive agent conductive carbon black (SP) was added into the stirring tank, and the revolution speed was 25 rpm, the rotation speed was 2000 rpm, the temperature was 40°C, and the stirring time was 120 minutes, so that the vacuum degree of the mixed system was ≤-0.085 MPa, and a conductive adhesive was prepared; wherein the specific surface area of ​​the first solid conductive agent was 100 m 2 / g, and particle size D50 is 35nm.

[0090] (3) Preparation of lithium manganese iron phosphate slurry

[0091] S1: Add 70kg LMFP (LMFP particle size is 2μm) and 4.5kg conductive glue into a stirring tank, with a revolution speed of 5rpm, a rotation speed of 800rpm, a temperature of 40°C, and a stirring time of 15 minutes;

[0092] S2: Add 9kg of conductive glue into the stirring tank, with a revolution speed of 5rpm, a rotation speed of 800rpm, a temperature of 40℃, and a stirring time of 15 minutes;

[0093] S3: Add 9kg of conductive glue into the stirring tank, with a revolution speed of 15rpm, a rotation speed of 1500rpm, a temperature of 40℃, and a stirring time of 10 minutes;

[0094] S4: revolution speed 25rpm, rotation speed 2000rpm, temperature 40°C, stirring time 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085Mpa;

[0095] S5: orbital speed: 15 rpm, rotation speed 300 rpm, stirring until the temperature drops to 25° C., so that the vacuum degree of the mixed system is ≤-0.085 MPa; obtaining lithium manganese iron phosphate slurry, the solid content of the lithium manganese iron phosphate slurry is 78%, and the viscosity is 6000 mPa·s.

[0096] 2. Preparation of ternary slurry

[0097] Step 1: Add 0.5 kg of the second conductive agent SP and 70 kg of NCM (the particle size of NCM is 6 μm) into a 100 L stirring tank, with a revolution speed of 25 rpm, a temperature of 45° C., and a stirring time of 15 minutes;

[0098] Step 2: Add 22.3 kg of solvent NMP into a stirring tank, with an orbital speed of 25 rpm, a rotation speed of 500 rpm, a temperature of 45°C, and a stirring time of 15 minutes;

[0099] Step 3: orbital speed 25 rpm, rotation speed 1500 rpm, temperature 45°C, stirring time 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0100] Step 4: Add 5kg of CNT conductive agent slurry into the stirring tank, with a revolution speed of 25rpm, a rotation speed of 1500rpm, a temperature of 45°C, and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085Mpa;

[0101] Step 5: Add 15.5 kg of the second glue solution into the stirring tank, with a revolution speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45°C, a stirring time of 90 minutes, and a vacuum degree of ≤-0.085 MPa;

[0102] Step 6: The mixture is stirred at an orbital speed of 15 rpm and an autorotational speed of 200 rpm until the temperature drops to 25° C. to obtain a ternary slurry having a solid content of 60.0% and a viscosity of 12000 mPa·s.

[0103] 3. Preparation of composite positive electrode slurry

[0104] (1) 14.6 kg NMP, 26.4 kg ternary slurry and 80 kg lithium iron manganese phosphate slurry were added into a 200 L stirring tank, with an orbital speed of 25 rpm, a rotation speed of 2000 rpm, a temperature of 45° C., and a stirring time of 120 minutes, so that the vacuum degree of the mixed system is ≤-0.085 MPa;

[0105] (2) The revolution speed was 20 rpm and the rotation speed was 1000 rpm, and the mixture was stirred until the temperature dropped to 25° C. to obtain the composite positive electrode slurry of this comparative example.

[0106] Comparative Example 3

[0107] This comparative example refers to Example 1 to prepare a composite positive electrode slurry. The difference between this comparative example and Example 1 is that in the process of preparing the ternary slurry, the amount of NCM added is adjusted to 85 kg, so that the solid content of the prepared ternary slurry is 81% and the viscosity is 11000 mPa·s. Except for the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0108] Comparative Example 4

[0109] This comparative example refers to Example 1 to prepare a composite positive electrode slurry. The difference between this comparative example and Example 1 is that in the process of preparing the ternary slurry, the amount of NCM added is adjusted to 50.5 kg so that the solid content of the prepared ternary slurry is 72% and the viscosity is 3000 mPa·s. Except for the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0110] Comparative Example 5

[0111] This comparative example refers to Example 1 to prepare a composite positive electrode slurry. The difference between this comparative example and Example 1 is that in the process of preparing the lithium manganese iron phosphate slurry, the amount of LMFP added is adjusted to 70.5 kg, so that the solid content of the prepared lithium manganese iron phosphate slurry is 72% and the viscosity is 23000 mPa·s. Except for the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0112] Comparative Example 6

[0113] This comparative example refers to Example 1 to prepare a composite positive electrode slurry. The difference between this comparative example and Example 1 is that in the process of preparing the lithium manganese iron phosphate slurry, the amount of LMFP added is adjusted to 49.3 kg, so that the solid content of the prepared lithium manganese iron phosphate slurry is 55% and the viscosity is 6500 mPa·s. Except for the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0114] Test Example 1

[0115] 1. Test object:

[0116] The composite positive electrode slurries prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were used as test objects in this test example.

[0117] 2. Test items:

[0118] (1) Solid content of composite positive electrode slurry: Place the composite positive electrode slurry to be tested in a pre-weighed container, and evaporate or volatilize the solvent in the liquid by heating or vacuum drying, leaving solid matter. Then weigh the mass of the solid matter and calculate the solid content.

[0119] (2) Fineness of composite positive electrode slurry: Take a spoonful of composite positive electrode slurry and place it on the scraper fineness gauge. Place the scraper horizontally on the upper end of the scraper fineness gauge so that the scraper is perpendicular to the surface of the scraper fineness gauge. Pull the scraper from the deep part of the groove to the shallow part at an appropriate speed and read the scale value where the particles are evenly exposed in the groove. The read value is the fineness of the composite positive electrode slurry.

[0120] (3) Initial viscosity and viscosity after 24 h of the composite cathode slurry: Install the viscometer so that the horizontal bubble of the body is placed in the black circle, immerse the rotor in the composite cathode slurry to the groove notch on the rotor rod, click Start, and read the viscosity value of the composite cathode slurry after the viscosity reading stabilizes.

[0121] 3. Test results:

[0122] Table 1 Performance test results of Examples 1 to 12 and Comparative Examples 1 to 6

[0123]

[0124]

[0125] The test results are shown in Table 1. By comparing the performance test results corresponding to Example 1 and Comparative Example 1, it can be found that the fineness and 24h viscosity change of the composite positive electrode slurry prepared in Comparative Example 1 are significantly higher than those in Example 1. The reason is that under the same conditions of other materials and operations for preparing the composite positive electrode slurry, Comparative Example 1 directly mixes NCM and LMFP. Since the particle size, structural characteristics and physical properties of lithium manganese iron phosphate and the ternary material are different, the direct physical mixing of the two main materials leads to uneven particle dispersion, low slurry stability and excessive viscosity in the subsequent unified slurry step, thereby significantly deteriorating the dispersibility and stability of the composite positive electrode slurry.

[0126] Comparing the performance test results corresponding to Example 1 and Comparative Example 2, it can be found that the fineness and 24h viscosity change of the composite positive electrode slurry prepared in Comparative Example 2 are significantly higher than those in Example 1. The reason is that under the same conditions of other materials and operations for preparing the composite positive electrode slurry, Comparative Example 2 adopts a semi-dry process to prepare NCM. Due to the large NCM particles, the solid content of the ternary slurry prepared by the semi-dry process is low, which is not conducive to maintaining a good van der Waals force between the conductive glue and the ternary material; LMFP is prepared by a wet process. Due to the small LMFP particles, large specific surface area, and strong adsorption capacity, the slurry homogenization is difficult, thereby significantly deteriorating the dispersibility and stability of the composite positive electrode slurry.

[0127] By comparing the performance test results corresponding to Example 1 and Comparative Examples 3 to 6, it can be found that the fineness and 24h viscosity change of the composite positive electrode slurry prepared in Comparative Examples 3 to 6 are significantly higher than those in Example 1. The reason is that under the same conditions of other materials and operations for preparing the composite positive electrode slurry, the solid content and viscosity of the ternary slurry prepared in Comparative Examples 3 and 4 are respectively too high and too low, and the solid content and viscosity of the lithium manganese iron phosphate slurry prepared in Comparative Examples 5 and 6 are respectively too high and too low, and the active particles are poorly dispersed in the slurry, and are easy to agglomerate and settle, thereby significantly deteriorating the dispersibility and stability of the composite positive electrode slurry.

[0128] The performance test results of Example 1 are compared with those of Examples 2 to 5. As shown in Table 1, under the same conditions of other materials and operations for preparing the composite positive electrode slurry, the solid content and viscosity of the ternary slurry in Example 4 are higher, and the solid content and viscosity of the ternary slurry in Example 5 are lower, and the fineness and 24h viscosity change of the composite positive electrode slurry obtained are higher than those of Examples 1 to 3. This shows that, compared with Examples 4 to 5, Examples 1 to 3 further control the solid content and viscosity of the ternary slurry, which is conducive to promoting uniform dispersion between different particles, thereby improving the dispersibility and stability of the composite positive electrode slurry.

[0129] The performance test results of Example 1 are compared with those of Examples 6 to 7. As shown in Table 1, under the same conditions of other materials and operations for preparing the composite positive electrode slurry, the first feeding amount of the conductive agent glue in S1 in the process of preparing the ternary slurry in Examples 6 and 7 is respectively low and high, and the fineness and 24h viscosity change of the composite positive electrode slurry obtained are higher than those in Example 1. This shows that, compared with Examples 6 to 7, Example 1 is conducive to fully wetting and dispersing the ternary material by adding the conductive glue to the ternary material step by step and reasonably setting the step-by-step feeding amount of the conductive glue, so that the uniformity and stability of the ternary slurry and the composite positive electrode slurry obtained are improved, and the particle agglomeration and sedimentation are prevented from adversely affecting the quality of the slurry.

[0130] By comparing the corresponding performance test results of Example 1 with those of Example 8, it can be found that the fineness and 24h viscosity change of the composite positive electrode slurry prepared in Example 8 are higher than those in Example 1. The reason is that under the same conditions of other materials and operations for preparing the composite positive electrode slurry, the first solid conductive agent used in the process of preparing the ternary slurry in Example 8 is carbon nanotubes. Since the carbon nanotubes have a small particle size and a large specific surface area, their dispersion effect is not good. They are directly introduced into the slurry in a solid form, resulting in uneven particle dispersion, reduced slurry stability, and increased viscosity, thereby deteriorating the dispersibility and stability of the composite positive electrode slurry.

[0131] The performance test results of Example 1 are compared with those of Examples 9 to 12. As shown in Table 1, under the same conditions of other materials and operations for preparing the composite positive electrode slurry, the solid content and viscosity of the lithium iron manganese phosphate slurry prepared in Example 11 are lower, and the solid content and viscosity of the lithium iron manganese phosphate slurry prepared in Example 12 are higher, and the fineness and 24h viscosity change of the composite positive electrode slurry obtained are higher than those of Example 1. This shows that, compared with Examples 9 to 10, Examples 1 and 11 to 12 further control the solid content and viscosity of the lithium iron manganese phosphate slurry, which is conducive to promoting uniform dispersion between different particles, thereby improving the dispersibility and stability of the composite positive electrode slurry.

[0132] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A method for homogenizing a composite positive electrode slurry, characterized in that: The method comprises the following operations: mixing the ternary slurry with the lithium iron manganese phosphate slurry to prepare a composite positive electrode slurry; The preparation method of the ternary slurry comprises the following operations: Adding conductive glue to the ternary material and stirring the mixture to obtain the ternary slurry, wherein the solid content of the ternary slurry is 76% to 80% and the viscosity is 4000 mPa·s to 7000 mPa·s; the conductive glue comprises a first glue and a first conductive agent; The method for preparing the lithium iron manganese phosphate slurry comprises the following operations: The lithium iron manganese phosphate and the second conductive agent are dry mixed and stirred to obtain a mixed dry material, and then the second glue is added to the mixed dry material to obtain the lithium iron manganese phosphate slurry. The lithium iron manganese phosphate slurry has a solid content of 58-62% and a viscosity of 7000-20000 mPa·s.

2. The method for homogenizing the composite positive electrode slurry according to claim 1, characterized in that: The first conductive agent includes at least one of a first solid conductive agent and a first conductive agent slurry; The specific surface area of ​​the first solid conductive agent is 50 m 2 / g~200m 2 / g, particle size D50 is 20nm~70nm; The specific surface area of ​​the solid conductive agent in the first conductive agent slurry is 100 m 2 / g~1000m 2 / g, and the particle size D50 is 4nm~17nm.

3. The method for homogenizing the composite positive electrode slurry according to claim 2, characterized in that: The first conductive agent includes a first solid conductive agent, and the mass ratio of the first glue solution to the first solid conductive agent is (45-50): (2-5), wherein the solid content of the first glue solution is 5.5-6.5%, and the viscosity is 1000mPa·s-1800mPa·s.

4. The method for homogenizing the composite positive electrode slurry according to claim 3, characterized in that: The mass ratio of the ternary material to the conductive adhesive is 70:(20-30).

5. The method for homogenizing the composite positive electrode slurry according to claim 4, characterized in that: The specific operation of adding the conductive glue to the ternary material is as follows: S1. Adding part of the conductive glue to the ternary material and stirring; S2. Add part of the conductive adhesive to the mixture obtained after S1 is completed and stir; S3. Add the remaining conductive adhesive to the mixed solution obtained after S2 is completed and stir to obtain the ternary slurry; Among them, the feeding amount of the conductive glue solution is determined according to the mass of the conductive glue solution described in S1: the mass of the conductive glue solution described in S2: the mass of the conductive glue solution described in S3 = (15-25): (35-45): (35-45).

6. The method for homogenizing the composite positive electrode slurry according to claim 1, characterized in that: The second glue has a solid content of 7% to 10% and a viscosity of 2000 to 4000 mPa·s.

7. The method for homogenizing the composite positive electrode slurry according to claim 6, characterized in that: Calculated by mass ratio, the lithium manganese iron phosphate: the second conductive agent: the second glue = 60: (0.2-0.8): (10-20).

8. The method for homogenizing the composite positive electrode slurry according to any one of claims 1 to 7, characterized in that: In the process of preparing the ternary slurry and / or the lithium iron manganese phosphate slurry, the temperature of the stirring treatment is 30-50°C.

9. The method for homogenizing the composite positive electrode slurry according to any one of claims 1 to 7, characterized in that: The particle size of the ternary material is 5 to 15 μm, and the particle size of the lithium manganese iron phosphate is 1 to 3 μm.

10. A composite positive electrode slurry, characterized in that: The composite positive electrode slurry is prepared by the homogenization method of any one of claims 1 to 9.

11. A lithium battery, characterized in that: It comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active coating, and the positive electrode active coating comprises the composite positive electrode slurry as claimed in claim 10.

Citation Information

Patent Citations

  • Mixed positive electrode material, positive plate using the same, and lithium ion battery

    CN104300123A

  • Method for processing ternary material by being clad with lithium ferric manganese phosphate

    CN105406069A

  • Safe lithium-ion secondary battery

    CN105449265A

  • Positive material, positive plate and lithium ion battery

    CN108777298A

  • Pulping method for ternary material for lithium-ion battery

    CN109378468A